The consumption of tortoise among Last Interglacial Iberian Neanderthals - Nabais, Mariana (2020)
Optimal foraging theory and diet breadth models often place large mammals in top-ranking positions due to their high-energy return. However, mass collection of small prey can result in comparable return rates, and dietary diversity is nutritionally beneficial on its own right. A growing body of evidence recovered from several sites in the Mediterranean Basin confirms Neanderthal use of small size prey. Slow-moving, tortoises are an easy catch, and human collection and consumption is demonstrated by taphonomic analysis. In Portugal, two key Middle Palaeolithic cave sites, Gruta da Oliveira and Gruta da Figueira Brava, provide pertinent evidence. Based on an improved osteometric method, in which long bone measurements are standardised and analysed together using the Logarithmic Size Index (LSI), it is possible to better gauge the contribution of tortoises to the diet and the human impact on the species’ populations. At inland Gruta da Oliveira, a tendency towards the massive collection of tortoises, affecting the local population more severely, is apparent. At coastal Gruta da Figueira Brava, the data suggest opportunistic collection upon encounter, possibly due to the availability of a more diverse range of resources.